Revitalizing Constitutional Law Learning through a Problem-Based Learning Approach in Legal Education - Hezron Sabar Rotua Tinambunan; Syahid Akhmad Faisol; Tevan Agus Setiawan; Firyal Nurul Badriyah; Anisa Deny Setiawati; Aditya Wiguna Sanjaya; Febrian Indar Surya Kusuma (Realism: Law Review, 2025)
Textbooks are a crucial component in higher education as primary learning resources that support conceptual understanding and analytical skills. In legal education, their role extends to shaping systematic and critical legal reasoning. However, the availability of textbooks aligned with the Semester Learning Plan (RPS) remains limited, particularly in Constitutional Law courses, resulting in fragmented and less contextual learning experiences. This study aims to develop and test a Problem-Based Learning (PBL)-based Constitutional Law textbook integrated with legal protection and human rights perspectives. The research employs an experimental design by implementing a prototype textbook in the Undergraduate Law Program, Campus 5, State University of Surabaya, and collecting feedback from students and experts. The results indicate that the developed textbook enhances students' critical thinking, analytical skills, and understanding of constitutional issues, especially those related to legal protection and human rights. The PBL approach encourages active learning through case analysis and problem-solving activities, making the learning process more contextual and participatory. This study contributes both theoretically and practically to the development of innovative, adaptive, and context-based legal education materials that support academic competitiveness.